IRS1/β‐Catenin Axis Is Activated and Induces MYC Expression in Acute Lymphoblastic Leukemia Cells. Issue 7 (15th March 2017) - Fernandes, Jaqueline Cristina; Rodrigues Alves, Ana Paula Nunes; Machado‐Neto, João Agostinho; Scopim‐Ribeiro, Renata; Fenerich, Bruna Alves; da Silva, Fernanda Borges; Simões, Belinda Pinto; Rego, Eduardo Magalhães; Traina, Fabiola
ABSTRACT: Insulin‐like growth factor 1 (IGF1) and its receptor IGF1R regulate normal cell growth and contribute to cell transformation through activation of downstream signaling pathways. In fibroblast cells, insulin receptor substrate 1 (IRS1), through IGF1 signaling, was found to be the key protein for nuclear translocation of β‐catenin and MYC transcription activation. We herein investigated the IRS1/β‐catenin axis in acute lymphoblastic leukemia (ALL) cells. Samples were obtained from 45 patients with ALL and 13 healthy donors. ALL cell lines were used. Gene expression was measured by quantitative PCR. Protein expression, associations, and cellular localization were evaluated by immunoprecipitation, subcellular fractionation, and confocal microscopy. Cells were submitted to IGF1 stimulation and/or IGF1R pharmacological inhibition (OSI‐906). IRS1, β‐catenin, and MYC mRNA expression were significantly elevated in ALL patients, compared to normal controls. MYC mRNA expression positively correlated with β‐catenin and IRS1 . Increased age and MYC expression negatively affected overall survival by univariate analysis. Total and phospho‐IGF1R and IRS1, MYC and β‐catenin protein expression were higher in ALL cells, compared to normal peripheral blood mononuclear cells (PBMC). IRS1 and β‐catenin were found to be colocalized in the nuclei and the cytoplasm of ALL cell lines, whereas both proteins were only slightly detected in the cytoplasm of normal PBMC. In Jurkat cells, a constitutive IRS1 and β‐catenin protein interaction were observed; OSI‐906 treatment decreased IGF1R tyrosine phosphorylation, IRS1 expression and phosphorylation, nuclear translocation of β‐catenin, IRS1 and β‐catenin association, and MYC protein expression. In conclusion, the IRS1/β‐catenin axis is activated in ALL cells. J. Cell. Biochem. 118: 1774–1781, 2017. © 2016 Wiley Periodicals, Inc. Abstract : IGF1R, IRS1, β‐catenin, and MYC are highly expressed in acute lymphoblast leukemia. IGF1 modulates β‐catenin nuclear translocation and MYC expression in ALL cells. IRS1/β‐catenin axis is activated and may contribute to MYC expression in ALL cells.